Acute Brain-Derived Neurotrophic Factor DNA Methylation Trajectories in Cerebrospinal Fluid and Associations With Outcomes Following Severe Traumatic Brain Injury in Adults. (September 2021) - Treble-Barna, Amery; Heinsberg, Lacey W.; Puccio, Ava M.; Shaffer, John R.; Okonkwo, David O.; Beers, Sue R.; Weeks, Daniel E.; Conley, Yvette P.
Background . Epigenetic biomarkers have the potential to explain outcome heterogeneity following traumatic brain injury (TBI) but are largely unexplored. Objective . This exploratory pilot study characterized brain-derived neurotrophic factor ( BDNF ) DNA methylation trajectories following severe TBI. Methods . Brain-derived neurotrophic factor DNA methylation trajectories in cerebrospinal fluid (CSF) over the first 5 days following severe TBI in 112 adults were examined in association with 3- and 12-month outcomes. Results . Group-based trajectory analysis revealed low and high DNA methylation groups at two BDNF cytosine-phosphate-guanine (CpG) targets that showed suggestive associations ( P < .05) with outcomes. Membership in the high DNA methylation groups was associated with better outcomes after controlling for age, sex, and injury severity. Associations of age × trajectory group interactions with outcomes at a third CpG site revealed a pattern of the same or better outcomes with higher ages in the high DNA methylation group and worse outcomes with higher ages in the low DNA methylation group. Conclusions . Although no observed associations met the empirical significance threshold after correcting for multiple comparisons, suggestive associations of the main effect models were consistent in their direction of effect and were observed across two CpG sites and two outcome time points. Results suggest that higher acute CSF BDNF DNA methylation may promote recovery following severe TBI in adults, and this effect may be more robust with higher age. While the results require replication in larger and racially diverse independent samples, BDNF DNA methylation may serve as an early postinjury biomarker helping to explain outcome heterogeneity following TBI.